Developing assessment instrument of qirÄatul kutub at islamic boarding school - Wahyuni, Ajeng; Kartowagiran, Badrun (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2018)
The purpose of this study was to develop and describe the quality and characteristics of an assessment instrument of by name of QirÄatul Kutub. This development research is based on Borg & Gall model. The steps of the development were (1) planning, (2) primary developing product, (3) preliminary field testing, (4) main field testing, and (5) final product revision. The subjects for preliminary field testing were 28 testees for performance test instrument and 96 testees for grammar mastery test derived from students of Darul Huda Islamic Boarding School, whereas the subjects for main field testing were 80 students for performance test instrument and 425 students for grammar mastery test. The research instruments were assessment instrument of QirÄatul Kutub which consisted of performance assessment instrument and grammar mastery essay test, observation and interview guide. The research data were analyzed based on Rasch Model. The results showed that: (1) the results of the development were 12 items of the performance test and 17 items of the grammar mastery test which were fit with the proposed model, (2) the item difficulty of the performance test ranged from -1.32 to 0.99, while for the grammar mastery test from -1.13 to 1.01; (3) the person reliability for the performance test was 0.86, item reliability was 0.97, and Cronbach's alpha value was 0.97. The grammar mastery test has person reliability 0.97 and item reliability 0.99 with Cronbach's alpha 0.90; (4) based on the test information function (TIF) and Standard Error of Measurement (SEM), the instruments were found to be good; the performance test and the grammar mastery test were suitable for learners with ability masteries between -4 and 4.